Designed synthesis of coaxial SnO2@carbon hollow nanospheres for highly reversible lithium storage - Li, Chang Ming (2012)
A proof-of-concept structural design is demonstrated for high-capacity lithium-ion batteries anode materials by multistep synthesis of coaxial SnO2@carbon hollow nanospheres. This material integrates two beneficial features: hollow structure and carbon nanopainting. When evaluated for reversible lithium storage, these functional materials manifest excellent cycling performance and rate capabilities.